A graphene oxide coated tapered microfiber acting as a super-sensor for rapid detection of SARS-CoV-2. Issue 12 (7th May 2021) - Jia, Hao; Zhang, Ao; Yang, Yuquan; Cui, Yaqi; Xu, Jianrong; Jiang, Hewei; Tao, Shengce; Zhang, Dawei; Zeng, Heping; Hou, Zhaoyuan; Feng, Jijun
Abstract : COVID-19 is a new strain of highly contagious coronavirus. Now, an innovative approach to detect it by combining DNA/RNA oligomers as aptamers and a GO coated optical microfiber as a sensor system. Abstract : COVID-19 is a new strain of highly contagious coronavirus, and at present, more than 221.4 million people have been infected with this virus, and the death toll exceeds 2793398. Early and fast detection of COVID-19 from infected individuals is critical to limit its spreading. Here, we report an innovative approach to detect the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleocapsid (N) protein by combining DNA/RNA oligomers as aptamers and a graphene oxide (GO) coated optical microfiber as a sensor system. The DNA/RNA aptamers can effectively capture the SARS-CoV-2 N protein in vitro, with the GO coated optical microfiber aptasensor for real-time monitoring of the SARS-CoV-2 N protein. Due to the extremely high surface-to-volume ratio and excellent optical and biochemical properties of the GO surface layer, the fixing effect of the microfiber surface is significantly improved and the lowest limit of detection (LOD) is 6.25 × 10 −19 M. Furthermore, in order to prove the feasibility of this sensing method in clinical applications, we use this sensor to detect the N protein mixed in fetal bovine serum (FBS) samples. The experimental results show that the biosensor can quickly and effectively detect the N protein (1 × 10 −9 M) in a complex sample matrix within 3 minutes. These findings suggest that this approach can be utilized for quantitative monitoring of coronavirus particles due to its high sensitivity, which can help to quickly exclude patients who do not have the infection. Collectively, the optical microfiber sensor system could be expected to become an important platform for the diagnosis of coronavirus due to its simple detection scheme and easy miniaturization.